Systemic Acquired Resistance and Salicylic Acid: Past, Present, and Future - Klessig, Daniel F.; Choi, Hyong Woo; Dempsey, D’Maris Amick (Molecular plant-microbe interactions, 2018)
This article is part of the Distinguished Review Article Series in Conceptual and Methodological Breakthroughs in Molecular Plant-Microbe Interactions. Salicylic acid (SA) is a critical plant hormone that regulates numerous aspects of plant growth and development as well as the activation of defenses against biotic and abiotic stress. Here, we present a historical overview of the progress that has been made to date in elucidating the role of SA in signaling plant immune responses. The ability of plants to develop acquired immunity after pathogen infection was first proposed in 1933. However, most of our knowledge about plant immune signaling was generated over the last three decades, following the discovery that SA is an endogenous defense signal. During this timeframe, researchers have identified i) two pathways through which SA can be synthesized, ii) numerous proteins that regulate SA synthesis and metabolism, and iii) some of the signaling components that function downstream of SA, including a large number of SA targets or receptors. In addition, it has become increasingly evident that SA does not signal immune responses by itself but, rather, as part of an intricate network that involves many other plant hormones. Future efforts to develop a comprehensive understanding of SA-mediated immune signaling will therefore need to close knowledge gaps that exist within the SA pathway itself as well as clarify how crosstalk among the different hormone signaling pathways leads to an immune response that is both robust and optimized for maximal efficacy, depending on the identity of the attacking pathogen.